In Situ and Real-Time Monitoring of Doping Levels by Reflectance Anisotropy Spectroscopy (RAS) during Molecular Beam Epitaxial (MBE) Growth of III/V Semiconductors - Henning Fouckhardt; Johannes Richter; Christoph Doering; Johannes Strassner (Advances in Materials Science and Engineering)
Reflectance anisotropy/difference spectroscopy (RAS/RDS) had been developed for monitoring epitaxial semiconductor growth, especially for the metal-organic chemical vapor deposition (MOCVD) of III/V semiconductors. But RAS is also well suited for the control of III/V growth with molecular beam epitaxy (MBE). Although the work on RAS has already started at least three decades ago, the potential of this in situ and real-time monitoring technique, especially for doping control, is not well known yet. Experimental results are given here on the identification of doping types and concentration during MBE growth, exemplarily for GaAs and AlGaAs. Especially, the dependence of the majority charge carrier concentration (i.e., the doping concentration) on the RAS signal difference between the nondoping and doping cases is addressed here.